Pendekatan Tafsir Maudhu’i Mengenai Jilbab dan Cadar dalam Perspektif Islam - Ismail, Fadhil; Nurliansyah, Sadiyah; Fahkira, Siti Namirah; Rubai'ah, Yunita; Zuhryan, Juone; Maulana, Elendi (Jurnal Penelitian Multidisiplin Ilmu, 2025)
This study discusses the concept of covering the genitals, focusing on the practice of wearing the hijab and niqab in an Islamic perspective with the Maudhu'i interpretation approach. This study uses a qualitative approach with a descriptive-analytical method based on related secondary sources, such as scientific articles, books, interpretations of the Qur'an and other research documents. This study examines QS. An-Nur verse 31 and QS. Al-Ahzab verse 59, which indicate the command to cover the genitals for Muslims. This study also discusses the social and cultural implications of the use of these clothes in society and the diversity of opinions among Islamic scholars regarding this matter.